Pengaruh Persepsi Kualitas, Citra Merek, Brand Wareness Pada Keputusan Pembelian Pada CV Pia Manalagi Ketapang Kota Probolinggo - Muhammad Syarif Hidayatullah Elmas (RELASI : JURNAL EKONOMI, 2020)
Based on research to know the effectof perception the quality, brand image, brand awareness trhadap decision the purchase by consumers CV.Pia Manalagi Ketapang ProbolinggoCity.Population research every consumer CV.Pia Manalagi Ketapang ProbolinggoCity.Sample consist of 30 respondents to technique incidental sampling.The method of analysis data using the validity, reliability test, regression analysis linear multiple and analysisthe coefficients determination.Based on the results of the testing of hypotheses done can be concluded that variable perception the quality, image brands and brand awareness based partial having influence a positive and significant on the decision the purchase CV.Pia Manalagi Ketapang ProbolinggoCity.The coefficients analysis determination show 69,7 % decision buy effectby perception the quality, brand image, brand awareness. Keywords: Perception of quality, brand image, brand awareness, purchasing decision